Environmental Controls on Crenarchaeol Distributions in Hydrothermal Springs - Amanda N. Calhoun; Jerome Blewett; Daniel R. Colman; Maximiliano J. Amenabar; Carolynn M. Harris; Eric S. Boyd; Ann Pearson; William D. Leavitt (Environmental Microbiology, 2026)
Thermophilic archaea synthesise cellular membranes composed primarily of isoprenoid glycerol dibiphytanyl glycerol tetraethers (iGDGTs). Cells can adjust the packing of their lipids by increasing cyclopentyl ring production, thereby decreasing membrane permeability and fluidity to maintain cellular function at high temperature, acidic pH, or nutrient limitation. Archaea of the class Nitrososphaeria synthesise crenarchaeol, an iGDGT with four cyclopentyl rings and a cyclohexyl ring, the function of which is unknown. Structural modelling suggests the cyclohexyl ring may increase membrane fluidity, potentially optimising membranes for mesophilic conditions. To investigate the role of crenarchaeol in archaeal membranes in natural settings, we quantify iGDGT compositions of forty‐one thermal springs in Yellowstone National Park (YNP), USA, and contextualise these within a global compilation of thermal spring iGDGTs spanning pH values of 1.1–10.1 and temperatures of 16°C–95°C. Spring pH is the strongest predictor of both crenarchaeol relative abundance and the number of cyclopentyl rings per iGDGT. Crenarchaeol relative abundance exhibits a nonlinear relationship with pH and temperature, with highest relative abundances at pH 7.4 and 46°C, decreasing above and below these values. These observations indicate that the cyclohexyl ring of crenarchaeol optimises archaeal cellular membranes for circumneutral and moderate temperature environmental conditions.

Cross‐Feeding of Carbon and Nitrogen Between Aquificales and Thermus in Hot Springs - Lisa M. Keller; Daniel R. Colman; Andri Stefánsson; Eric S. Boyd (Environmental Microbiology, 2026)
Acquisition and cycling of carbon and nitrogen among members of hot spring communities are not well understood. Metagenomic analyses of 105 communities inhabiting high temperature hot springs across Yellowstone and Iceland showed a co‐distribution pattern of putatively autotrophic and/or diazotrophic (nitrogen‐fixing) Aquificales and Thermus populations. Targeted enrichment of autotrophic and diazotrophic populations in an Icelandic hot spring produced a co‐culture of Pampinifervens (Aquificales) that encoded carbon dioxide and nitrogen fixation pathways and Thermus (Thermales). Growth experiments revealed Pampinifervens could support the fixed carbon and nitrogen demands of Thermus , enabling growth. Interestingly, growth of Thermus was enhanced in co‐cultures when Pampinifervens was forced to fix both carbon and nitrogen versus just carbon (ammonia‐amended cultures). Further experimentation with Thermus , when grown in isolation, showed it preferred amino acids over ammonia as a nitrogen source. These findings demonstrate the importance of metabolic interactions among populations that can dictate the co‐distribution of taxa in hot springs, drive community assembly, and maintain biodiversity. Further, these results highlight the fundamental role of Aquificales in the functioning of hot spring ecosystems, particularly those limited in organic carbon and fixed nitrogen like those in Iceland and to a lesser extent Yellowstone.

Incubation duration and predicted hatchling sex ratios of leatherback turtles (Dermochelys coriacea) in the southwestern Atlantic Ocean (1988–2021) - Liliana P. Colman; Cecília Baptistotte; Brendan J. Godley; João C.A. Thomé; Ana C. Marcondes; Jonathan R. Monsinjon; Alexsandro Santos; Ana Rita Caldas Patrício; Gustavo Stahelin; Annette C. Broderick (Journal of Experimental Marine Biology and Ecology, 2025)

Acquisition of elemental sulfur by sulfur‐oxidising Sulfolobales - Maria C. Fernandes‐Martins; Carli Springer; Daniel R. Colman; Eric S. Boyd (Environmental Microbiology, 2024)
Elemental sulfur (S 8 0 )‐oxidising Sulfolobales (Archaea) dominate high‐temperature acidic hot springs (>80°C, pH 8 0 ‐oxidising members of the Sulfolobales reveal a patchy distribution of genes encoding sulfur oxygenase reductase (SOR), an S 8 0 disproportionating enzyme attributed to S 8 0 oxidation. Here, we report the S 8 0 ‐dependent growth of two Sulfolobales strains previously isolated from acidic hot springs in Yellowstone National Park, one of which associated with bulk S 8 0 during growth and one that did not. The genomes of each strain encoded different sulfur metabolism enzymes, with only one encoding SOR. Dialysis membrane experiments showed that direct contact is not required for S 8 0 oxidation in the SOR‐encoding strain. This is attributed to the generation of hydrogen sulfide (H 2 S) from S 8 0 disproportionation that can diffuse out of the cell to solubilise bulk S 8 0 to form soluble polysulfides (S x 2− ) and/or S 8 0 nanoparticles that readily diffuse across dialysis membranes. The Sulfolobales strain lacking SOR required direct contact to oxidise S 8 0 , which could be overcome by the addition of H 2 S. High concentrations of S 8 0 inhibited the growth of both strains. These results implicate alternative strategies to acquire and metabolise sulfur in Sulfolobales and have implications for their distribution and ecology in their hot spring habitats.

Correction: Limits to the three domains of life: lessons from community assembly along an Antarctic salinity gradient - Xiaoben Jiang; David J. Van Horn; Jordan G. Okie; Heather N. Buelow; Egbert Schwartz; Daniel R. Colman; Kelli L. Feeser; Cristina D. Takacs-Vesbach (Extremophiles, 2024)

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

The dynamic influence of subsurface geological processes on the assembly and diversification of thermophilic microbial communities in continental hydrothermal systems - Kenneth W.W. Sims; Cole M. Messa; Sean R. Scott; Andrew D. Parsekian; Andrew Miller; Abraham L. Role; Timothy P. Moloney; Everett L. Shock; Jacob B. Lowenstern; R. Blaine McCleskey; Matthew A. Charette; Bradley J. Carr; et al. (Geochimica et Cosmochimica Acta, 2023)

Tectonic and geological setting influence hot spring microbiology - Daniel R. Colman; Allison Veach; Andri Stefánsson; Louie Wurch; B. Shafer Belisle; Peter T. Podar; Zamin Yang; Dawn Klingeman; Kazuyo Senba; Katsuhiko S. Murakami; Jakob K. Kristjánsson; Snædís H. Björnsdóttir; et al. (Environmental Microbiology, 2023)
Hydrothermal systems form at divergent and convergent boundaries of lithospheric plates and within plates due to weakened crust and mantle plumes, playing host to diverse microbial ecosystems. Little is known of how differences in tectonic setting influence the geochemical and microbial compositions of these hydrothermal ecosystems. Here, coordinated geochemical and microbial community analyses were conducted on 87 high‐temperature (>65°C) water and sediment samples from hot springs in Yellowstone National Park, Wyoming, USA ( n = 41; mantle plume setting), Iceland ( n = 41, divergent boundary), and Japan ( n = 5; convergent boundary). Region‐specific variation in geochemistry and sediment‐associated 16S rRNA gene amplicon sequence variant (ASV) composition was observed, with 16S rRNA gene assemblages being nearly completely distinguished by region and pH being the most explanatory parameter within regions. Several low abundance ASVs exhibited cosmopolitan distributions across regions, while most high‐abundance ASVs were only identified in specific regions. The presence of some cosmopolitan ASVs across regions argues against dispersal limitation primarily shaping the distribution of taxa among regions. Rather, the results point to local tectonic and geologic characteristics shaping the geochemistry of continental hydrothermal systems that then select for distinct microbial assemblages. These results provide new insights into the co‐evolution of hydrothermal systems and their microbial communities.

Assessing the role of the gut microbiome in methylmercury demethylation and elimination in humans and gnotobiotic mice - Genevieve L. Coe; Ian N. Krout; Mason Munro-Ehrlich; Catherine R. Beamish; Daria Vorojeikina; Daniel R. Colman; Eric J. Boyd; Seth T. Walk; Matthew D. Rand (Archives of Toxicology, 2023)

Distribution and abundance of tetraether lipid cyclization genes in terrestrial hot springs reflect pH - Laura N. Blum; Daniel R. Colman; Emiley A. Eloe‐Fadrosh; Matthew Kellom; Eric S. Boyd; Olga Zhaxybayeva; William D. Leavitt (Environmental Microbiology, 2023)
Many Archaea produce membrane‐spanning lipids that enable life in extreme environments. These isoprenoid glycerol dibiphytanyl glycerol tetraethers (GDGTs) may contain up to eight cyclopentyl and one cyclohexyl ring, where higher degrees of cyclization are associated with more acidic, hotter or energy‐limited conditions. Recently, the genes encoding GDGT ring synthases, grsAB , were identified in two Sulfolobaceae; however, the distribution and abundance of grs homologs across environments inhabited by these and related organisms remain a mystery. To address this, we examined the distribution of grs homologs in relation to environmental temperature and pH, from thermal springs across Earth, where sequences derive from metagenomes, metatranscriptomes, single‐cell and cultivar genomes. The abundance of grs homologs shows a strong negative correlation to pH, but a weak positive correlation to temperature. Archaeal genomes and metagenome‐assembled genomes (MAGs) that carry two or more grs copies are more abundant in low pH springs. We also find grs in 12 archaeal classes, with the most representatives in Thermoproteia, followed by MAGs of the uncultured Korarchaeia, Bathyarchaeia and Hadarchaeia, while several Nitrososphaeria encodes >3 copies. Our findings highlight the key role of grs ‐catalysed lipid cyclization in archaeal diversification across hot and acidic environments.

Relationships between fluid mixing, biodiversity, and chemosynthetic primary productivity in Yellowstone hot springs - Maria C. Fernandes‐Martins; Daniel R. Colman; Eric S. Boyd (Environmental Microbiology, 2023)
The factors that influence biodiversity and productivity of hydrothermal ecosystems are not well understood. Here we investigate the relationship between fluid mixing, biodiversity, and chemosynthetic primary productivity in three co‐localized hot springs (RSW, RSN, and RSE) in Yellowstone National Park that have different geochemistry. All three springs are sourced by reduced hydrothermal fluid, but RSE and RSN receive input of vapour phase gas and oxidized groundwaters, with input of both being substantially higher in RSN. Metagenomic sequencing revealed that communities in RSN were more biodiverse than those of RSE and RSW in all dimensions evaluated. Microcosm activity assays indicate that rates of dissolved inorganic carbon (DIC) uptake were also higher in RSN than in RSE and RSW. Together, these results suggest that increased mixing of reduced volcanic fluid with oxidized fluids generates additional niche space capable of supporting increasingly biodiverse communities that are more productive. These results provide insight into the factors that generate and maintain chemosynthetic biodiversity in hydrothermal systems and that influence the distribution, abundance, and diversity of microbial life in communities supported by chemosynthesis. These factors may also extend to other ecosystems not supported by photosynthesis, including the vast subterranean biosphere and biospheres beneath ice sheets and glaciers.

Ascertainment rate of SARS-CoV-2 infections from healthcare and community testing in the UK - Ewan Colman; Gavrila A. Puspitarani; Jessica Enright; Rowland R. Kao (Journal of Theoretical Biology, 2023)

A naturalist perspective of microbiology: Examples from methanogenic archaea - Eric S. Boyd; Rachel L. Spietz; Manjinder Kour; Daniel R. Colman (Environmental Microbiology, 2023)
Storytelling has been the primary means of knowledge transfer over human history. The effectiveness and reach of stories are improved when the message is appropriate for the target audience. Oftentimes, the stories that are most well received and recounted are those that have a clear purpose and that are told from a variety of perspectives that touch on the varied interests of the target audience. Whether scientists realize or not, they are accustomed to telling stories of their own scientific discoveries through the preparation of manuscripts, presentations, and lectures. Perhaps less frequently, scientists prepare review articles or book chapters that summarize a body of knowledge on a given subject matter, meant to be more holistic recounts of a body of literature. Yet, by necessity, such summaries are often still narrow in their scope and are told from the perspective of a particular discipline. In other words, interdisciplinary reviews or book chapters tend to be the rarity rather than the norm. Here, we advocate for and highlight the benefits of interdisciplinary perspectives on microbiological subjects.

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Limits to the three domains of life: lessons from community assembly along an Antarctic salinity gradient - Xiaoben Jiang; David J. Van Horn; Jordan G. Okie; Heather N. Buelow; Egbert Schwartz; Daniel R. Colman; Kelli L. Feeser; Cristina D. Takacs-Vesbach (Extremophiles, 2022)

Seasonal hydrologic and geologic forcing drive hot spring geochemistry and microbial biodiversity - Daniel R. Colman; Melody R. Lindsay; Annette Harnish; Evan M. Bilbrey; Maximiliano J. Amenabar; Matthew J. Selensky; Kristopher M. Fecteau; Randall V. Debes; Matthew B. Stott; Everett L. Shock; Eric S. Boyd (Environmental Microbiology, 2021)
Summary Hot springs integrate hydrologic and geologic processes that vary over short‐ and long‐term time scales. However, the influence of temporal hydrologic and geologic change on hot spring biodiversity is unknown. Here, we coordinated near‐weekly, cross‐seasonal (~140 days) geochemical and microbial community analyses of three widely studied hot springs with local precipitation data in Yellowstone National Park. One spring (‘HFS’) exhibited statistically significant, coupled microbial and geochemical variation across seasons that was associated with recent precipitation patterns. Two other spring communities, ‘CP’ and ‘DS’, exhibited minimal to no variation across seasons. Variability in the seasonal response of springs is attributed to differences in the timing and extent of aquifer recharge with oxidized near‐surface water from precipitation. This influx of oxidized water is associated with changes in community composition, and in particular, the abundances of aerobic sulfide‐/sulfur‐oxidizers that can acidify waters. During sampling, a new spring formed after a period of heavy precipitation and its successional dynamics were also influenced by surface water recharge. Collectively, these results indicate that changes in short‐term hydrology associated with precipitation can impact hot spring geochemistry and microbial biodiversity. These results point to potential susceptibility of certain hot springs and their biodiversity to sustained, longer‐term hydrologic changes.

Trichoderma species show biocontrol potential against Ceratocystis wilt in mango plants - R. A. S. Brito; G. P. Cavalcante; V. M. Stock; A. A. Colman; D. P. dos Santos; R. A. Sermarini; L. A. Maffia (European Journal of Plant Pathology, 2020)

Characterization of functionalized bentonite as nanocarrier of salicylic acid with protective action against Pseudomonas syringae in tomato plants - Andrea Y. Mansilla; María F. Salcedo; Silvana L. Colman; Merari T. Chevalier; Matias R. Lanfranconi; Vera A. Alvarez; Claudia A. Casalongué (European Journal of Plant Pathology, 2020)

Monitoring human genotoxicity risk associated to urban and industrial Buenos Aires air pollution exposure - María de los A. Gutiérrez; Mónica A. Palmieri; Daniela S. Giuliani; Jorge E. Colman Lerner; Guillermo Maglione; Darío Andrinolo; Deborah R. Tasat (Environmental Science and Pollution Research, 2020)

Observed and projected intra‐seasonal variability of Australian monsoon rainfall - Aurel Moise; Ian Smith; Josephine R. Brown; Robert Colman; Sugata Narsey (International Journal of Climatology, 2020)
Indices derived from daily rainfall time series are used to measure “burst” features of the northern Australia monsoon, corresponding to one or more days of heavy rainfall. These indices include number of burst days, numbers and durations of burst events, and average intensity. The results using observational data show how these features can vary from one year to the next, and how they can vary from the station scale (Darwin) to the regional scale (northern Australia). The results from Coupled Model Intercomparison Project Phase 5 (CMIP5) climate model simulations under both historical and future greenhouse gas conditions have also been analysed and indicate how well models can capture these features and how they might change by the end of the 21st century under a high emissions scenario. While most models provide a reasonable simulation of present‐day burst features, there is little consensus for a significant change to seasonal rainfall totals when looking at the full CMIP5 ensemble. A subset of models with detectable skills with respect to the Madden‐Julian Oscillation shows evidence for an increase in the seasonal total rainfall amount and most other monsoon metrics, except a slight decrease in the number of burst events. This is consistent with a basic thermodynamic response to warming and consistent with findings elsewhere. However, the Australian monsoon is strongly influenced by the large‐scale circulation and there remains some doubt about whether we can confidently diagnose all the changes to monsoon bursts that could occur given the limited ability of many of the current generation of models to simulate tropical cyclones, the Madden‐Julian Oscillation and other relevant features.

Assessing coastal artificial light and potential exposure of wildlife at a national scale: the case of marine turtles in Brazil - Liliana P. Colman; Paulo H. Lara; Jonathan Bennie; Annette C. Broderick; Juliana R. de Freitas; Ana Marcondes; Matthew J. Witt; Brendan J. Godley (Biodiversity and Conservation, 2020)
Coastal areas provide critical nesting habitat for marine turtles. Understanding how artificial light might impact populations is key to guide management strategies. Here we assess the extent to which nesting populations of four marine turtle species—leatherback ( Dermochelys coriacea ), olive ridley ( Lepidochelys olivacea ), hawksbill ( Eretmochelys imbricata ) and two subpopulations of loggerhead ( Caretta caretta ) turtles—are exposed to light pollution across 604 km of the Brazilian coast. We used yearly night-time satellite images from two 5-year periods (1992–1996 and 2008–2012) from the US Air Force Defense Meteorological Satellite Programme (DMSP) to determine the proportion of nesting areas that are exposed to detectable levels of artificial light and identify how this has changed over time. Over the monitored time-frame, 63.7% of the nesting beaches experienced an increase in night light levels. Based on nest densities, we identified 54 reproductive hotspots: 62.9% were located in areas potentially exposed to light pollution. Light levels appeared to have a significant effect on nest densities of hawksbills and the northern loggerhead turtle stock, however high nest densities were also seen in lit areas. The status of all species/subpopulations has improved across the time period despite increased light levels. These findings suggest that (1) nest site selection is likely primarily determined by variables other than light and (2) conservation strategies in Brazil appear to have been successful in contributing to reducing impacts on nesting beaches. There is, however, the possibility that light also affects hatchlings in coastal waters, and impacts on population recruitment may take longer to fully manifest in nesting numbers. Recommendations are made to further this work to provide deeper insights into the impacts of anthropogenic light on marine turtles.

Informing CITES Parties: Strengthening science‐based decision‐making when listing marine species - Kim Friedman; Matias Braccini; Matthew Bjerregaard‐Walsh; Ramón Bonfil; Corey J. A. Bradshaw; Stephen Brouwer; Ian Campbell; Rui Coelho; Enric Cortés; Wetjens Dimmlich; Michael G. Frisk; Irene Kingma; et al. (Fish and Fisheries, 2020)
International trade in vulnerable marine species is regulated once they are listed in CITES Appendices (the Convention on International Trade in Endangered Species of Wild Fauna and Flora). Parties to the Convention submit proposal(s) 150 days prior to the CITES Conference for voting on the inclusion of new species in Appendices I and II, making a case for why CITES listing criteria are met in each case. Before the vote, Parties receive advice from (a) the Food and Agriculture Organization of the United Nations, (b) the International Union for Conservation of Nature—TRAFFIC and (c) the CITES Secretariat, among others. This paper offers an expert review of listing processes, which are the subject of much debate in fishery and environment‐protection communities, looking at two specific cases: silky shark ( Carcharhinus falciformis, Carcharhinidae) and bigeye thresher shark ( Alopias superciliosus, Alopiidae). The reviewers determine that the evidence made available to voting Parties is substantial, but suffers from non‐standard presentation across assessments. The best available data are not always presented or described transparently in relation to CITES criteria. An extension of the assessment period, as well as the opportunity to refute evidence, has been suggested as ways to support more informed and effective decision‐making by CITES Parties, whose composition of delegations varies greatly in their experience of marine species management and trade. Experts welcomed a greater coherence of advice between fishery and non‐fishery sources in the long term, and proposed a range of suggested improvements for the delivery of information and advice to CITES Parties.

Geologic legacy spanning >90 years explains unique Yellowstone hot spring geochemistry and biodiversity - Devon Payne; Eric C. Dunham; Elizabeth Mohr; Isaac Miller; Adrienne Arnold; Reece Erickson; Elizabeth M. Fones; Melody R. Lindsay; Daniel R. Colman; Eric S. Boyd (Environmental Microbiology, 2019)
Summary Little is known about how the geological history of an environment shapes its physical and chemical properties and how these, in turn, influence the assembly of communities. Evening primrose (EP), a moderately acidic hot spring (pH 5.6, 77.4°C) in Yellowstone National Park (YNP), has undergone dramatic physicochemical change linked to seismic activity. Here, we show that this legacy of geologic change led to the development of an unusual sulphur‐rich, anoxic chemical environment that supports a unique archaeal‐dominated and anaerobic microbial community. Metagenomic sequencing and informatics analyses reveal that >96% of this community is supported by dissimilatory reduction or disproportionation of inorganic sulphur compounds, including a novel, deeply diverging sulphate‐reducing thaumarchaeote. When compared to other YNP metagenomes, the inferred functions of EP populations were like those from sulphur‐rich acidic springs, suggesting that sulphur may overprint the predominant influence of pH on the composition of hydrothermal communities. Together, these observations indicate that the dynamic geological history of EP underpins its unique geochemistry and biodiversity, emphasizing the need to consider the legacy of geologic change when describing processes that shape the assembly of communities.

Probing the geological source and biological fate of hydrogen in Yellowstone hot springs - Melody R. Lindsay; Daniel R. Colman; Maximiliano J. Amenabar; Kirsten E. Fristad; Kristopher M. Fecteau; Randall V. Debes; John R. Spear; Everett L. Shock; Tori M. Hoehler; Eric S. Boyd (Environmental Microbiology, 2019)
Summary Hydrogen (H 2 ) is enriched in hot springs and can support microbial primary production. Using a series of geochemical proxies, a model to describe variable H 2 concentrations in Yellowstone National Park (YNP) hot springs is presented. Interaction between water and crustal iron minerals yields H 2 that partition into the vapour phase during decompressional boiling of ascending hydrothermal fluids. Variable vapour input leads to differences in H 2 concentration among springs. Analysis of 50 metagenomes from a variety of YNP springs reveals that genes encoding oxidative hydrogenases are enriched in communities inhabiting springs sourced with vapour‐phase gas. Three springs in the Smokejumper (SJ) area of YNP that are sourced with vapour‐phase gas and with the most H 2 in YNP were examined to determine the fate of H 2 . SJ3 had the most H 2 , the most 16S rRNA gene templates and the greatest abundance of culturable hydrogenotrophic and autotrophic cells of the three springs. Metagenomics and transcriptomics of SJ3 reveal a diverse community comprised of abundant populations expressing genes involved in H 2 oxidation and carbon dioxide fixation. These observations suggest a link between geologic processes that generate and source H 2 to hot springs and the distribution of organisms that use H 2 to generate energy.

Isotope ecology detects fine-scale variation in Svalbard reindeer diet: implications for monitoring herbivory in the changing Arctic - Lily Z. Zhao; Albert S. Colman; R. Justin Irvine; Stein Rune Karlsen; Gerard Olack; Erik A. Hobbie (Polar Biology, 2019)

Electron acceptor availability alters carbon and energy metabolism in a thermoacidophile - Maximiliano J. Amenabar; Daniel R. Colman; Saroj Poudel; Eric E. Roden; Eric S. Boyd (Environmental Microbiology, 2018)
Summary The thermoacidophilic Acidianus strain DS80 displays versatility in its energy metabolism and can grow autotrophically and heterotrophically with elemental sulfur (S°), ferric iron (Fe 3+ ) or oxygen (O 2 ) as electron acceptors. Here, we show that autotrophic and heterotrophic growth with S° as the electron acceptor is obligately dependent on hydrogen (H 2 ) as electron donor; organic substrates such as acetate can only serve as a carbon source. In contrast, organic substrates such as acetate can serve as electron donor and carbon source for Fe 3+ or O 2 grown cells. During growth on S° or Fe 3+ with H 2 as an electron donor, the amount of CO 2 assimilated into biomass decreased when cultures were provided with acetate. The addition of CO 2 to cultures decreased the amount of acetate mineralized and assimilated and increased cell production in H 2 /Fe 3+ grown cells but had no effect on H 2 /S° grown cells. In acetate/Fe 3+ grown cells, the presence of H 2 decreased the amount of acetate mineralized as CO 2 in cultures compared to those without H 2 . These results indicate that electron acceptor availability constrains the variety of carbon sources used by this strain. Addition of H 2 to cultures overcomes this limitation and alters heterotrophic metabolism.

On the influence of simulated SST warming on rainfall projections in the Indo-Pacific domain: an AGCM study - Huqiang Zhang; Y. Zhao; A. Moise; H. Ye; R. Colman; G. Roff; M. Zhao (Climate Dynamics, 2018)

Limits to global and Australian temperature change this century based on expert judgment of climate sensitivity - Michael R. Grose; Robert Colman; Jonas Bhend; Aurel F. Moise (Climate Dynamics, 2017)

Wildlife response to infrastructure: the problem with confounding factors - Jonathan E. Colman; Tine Bergmo; Diress Tsegaye; Kjetil Flydal; Sindre Eftestøl; Marte S. Lilleeng; Stein R. Moe (Polar Biology, 2017)

Uncertainty in CMIP5 model-projected changes in the onset/retreat of the Australian summer monsoon - Huqiang Zhang; Guangtao Dong; A. Moise; R. Colman; L. Hanson; H. Ye (Climate Dynamics, 2016)

Detection and analysis of elusive members of a novel and diverse archaeal community within a thermal spring streamer consortium - Daniel R. Colman; Raquela Thomas; Kendra R. Maas; Cristina D. Takacs-Vesbach (Extremophiles, 2015)

The South Pacific Convergence Zone in CMIP5 simulations of historical and future climate - Josephine R. Brown; Aurel F. Moise; Robert A. Colman (Climate Dynamics, 2013)

On atmospheric radiative feedbacks associated with climate variability and change - R. A. Colman; L. I. Hanson (Climate Dynamics, 2013)

Antimicrobial effects of commercial silver nanoparticles are attenuated in natural streamwater and sediment - Benjamin P. Colman; Si-Yi Wang; Melanie Auffan; Mark R. Wiesner; Emily S. Bernhardt (Ecotoxicology, 2012)

Do diet and taxonomy influence insect gut bacterial communities? - D. R. Colman; E. C. Toolson; C. D. Takacs‐Vesbach (Molecular Ecology, 2012)
Many insects contain diverse gut microbial communities. While several studies have focused on a single or small group of species, comparative studies of phylogenetically diverse hosts can illuminate general patterns of host–microbiota associations. In this study, we tested the hypotheses that (i) host diet and (ii) host taxonomy structure intestinal bacterial community composition among insects. We used published 16S rRNA gene sequence data for 58 insect species in addition to four beetle species sampled from the S evilleta N ational W ildlife R efuge to test these hypotheses. Overall, gut bacterial species richness in these insects was low. Decaying wood xylophagous insects harboured the richest bacterial gut flora (102.8 species level operational taxonomic units ( OTU s)/sample ± 71.7, 11.8 ± 5.9 phylogenetic diversity ( PD )/sample), while bees and wasps harboured the least rich bacterial communities (11.0 species level OTU s/sample ± 5.4, 2.6 ± 0.8 PD /sample). We found evidence to support our hypotheses that host diet and taxonomy structure insect gut bacterial communities ( P

Symbiodinium diversity in the soft coral Heteroxenia sp. and its nudibranch predator Phyllodesmium lizardensis - S. K. FitzPatrick; K. L. Liberatore; J. R. Garcia; I. Burghardt; D. R. Colman; S. A. Moquin; C. D. Takacs-Vesbach; U. L. Shepherd (Coral Reefs, 2012)

Multiple Effects of Changes in Arctic Snow Cover - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Raymond S. Bradley; Sylvie Blangy; Olga N. Bulygina; Torben R. Christensen; Jonathan E. Colman; Richard L. H. Essery; et al. (Ambio, 2011)

On tropospheric adjustment to forcing and climate feedbacks - R. A. Colman; B. J. McAvaney (Climate Dynamics, 2011)

Polar lipid remodeling and increased sulfatide expression are associated with the glioma therapeutic candidates, wild type p53 elevation and the topoisomerase-1 inhibitor, Irinotecan - Huan He; Carol L. Nilsson; Mark R. Emmett; Yongjie Ji; Alan G. Marshall; Roger A. Kroes; Joseph R. Moskal; Howard Colman; Frederick F. Lang; Charles A. Conrad (Glycoconjugate Journal, 2010)

On the contribution of local feedback mechanisms to the range of climate sensitivity in two GCM ensembles - M. J. Webb; C. A. Senior; D. M. H. Sexton; W. J. Ingram; K. D. Williams; M. A. Ringer; B. J. McAvaney; R. Colman; B. J. Soden; R. Gudgel; T. Knutson; S. Emori; et al. (Climate Dynamics, 2006)

A comparison of climate feedbacks in general circulation models - R. Colman (Climate Dynamics, 2003)

Seasonal contributions to climate feedbacks - R. Colman (Climate Dynamics, 2003)

Regulation of CD11b/CD18 (Mac-1) adhesion to fibrinogen by urokinase receptor (uPAR) - H. Zhang; R. W. Colman; N. Sheng (Inflammation Research, 2003)

Birth of the modern Chesapeake Bay estuary between 7.4 and 8.2 ka and implications for global sea-level rise - John F. Bratton; Steven M. Colman; E. Robert Thieler; Robert R. Seal (Geo-Marine Letters, 2002)

STOIC: a study of coupled model climatology and variability in tropical ocean regions - Davey M.; Huddleston M.; Sperber K.; Braconnot P.; Bryan F.; Chen D.; Colman R.; Cooper C.; Cubasch U.; Delecluse P.; DeWitt D.; Fairhead L.; et al. (Climate Dynamics, 2002)

ENSIP: the El Niño simulation intercomparison project - M. Latif; K. Sperber; J. Arblaster; P. Braconnot; D. Chen; A. Colman; U. Cubasch; C. Cooper; P. Delecluse; D. Dewitt; L. Fairhead; G. Flato; et al. (Climate Dynamics, 2001)

Climate feedbacks in a general circulation model incorporating prognostic clouds - R. Colman; J. Fraser; L. Rotstayn (Climate Dynamics, 2001)

Aircraft Measurements of Dimethyl Sulfide (DMS) Using a Whole Air Sampling Technique - I. J. Simpson; J. J. Colman; A. L. Swanson; A. R. Bandy; D. C. Thornton; D. R. Blake; F. S. Rowland (Journal of Atmospheric Chemistry, 2001)

Bradykinin receptor antagonists type 2 attenuate the inflammatory changes in peptidoglycan-induced acute arthritis in the Lewis rat - A.B. Uknis; R.A. DeLa Cadena; R. Janardham; R.B. Sartor; E.T. Whalley; R.W. Colman (Inflammation Research, 2001)

On the vertical extent of atmospheric feedbacks - R. A. Colman (Climate Dynamics, 2001)

Non-linear climate feedback analysis in an atmospheric general circulation model - R. A. Colman; S. B. Power; B. J. McAvaney (Climate Dynamics, 1997)